Altered physiochemical properties in industrially synthesized ZnO nanoparticles regulate oxidative stress; induce in vivo cytotoxicity in embryonic zebrafish by apoptosis. Issue 1 (December 2017) - Verma, Suresh; Panda, Pritam; Jha, Ealisha; Suar, Mrutyunjay; Parashar, S.
Abstract This study investigates thein vivo cytotoxicity of ZnO nanoparticles synthesized at industrial scale with embryonic Zebrafish. Industrial synthesis of ZnO nanoparticles was mimicked at lab scale by high energy ball milling technique by milling bulk ZnO particles for 15 h. Synthesized 7 h and 10 h ZnO nanoparticles showed significant alteration of size, zeta potential and optical properties in comparison to Bulk ZnO. Mortality and hatching rate in Zebrafish embryos were influenced by these alterations. Size and charge dependent effect of ZnO nanoparticles exposure on physiology and development of Zebrafish embryos were evident by malfunctioned organ development and abnormal heartbeat rate. Similar dependency on quenching of ROS due to influential hydrogen bond interaction with glycine residue of Sod1 oxidative stress protein and increased apoptosis were observed in cells. The study revealed the mechanism of cytotoxicity in exposed embryonic Zebrafish as an effect of accumulation and internalization inside cells instigating to generation of hypoxic condition and interference with the normal adaptive stress regulation signaling pathways leading towards enhanced apoptosis. The study revealed hidden size and charge dependentin vivo cytotoxicity mechanism of ZnO nanoparticles in Zebrafish embryos insight of the environmental and clinical importance of attention on industrially synthesized ZnO nanoparticles.